2019
DOI: 10.1111/infi.12355
|View full text |Cite
|
Sign up to set email alerts
|

Emerging market capital flows and U.S. monetary policy

Abstract: This paper analyzes the drivers of net private capital flows to emerging market economies (EMEs), focusing in particular on the policies of the Federal Reserve. We argue that the role of the Federal Reserve in EME capital flows has been smaller than popularly believed. We first show that the run‐up in capital flows to EMEs predated the loosening of Fed policy, while flows slowed substantially between 2010 and 2015, even as the Fed's quantitative easing program continued to add to monetary stimulus. Both the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…First, surges are very poorly explained by global factors even in the pre-GFC period for advanced economies, while they do explain EME surges. Second, the drop of explanatory power of monetary policy post-GFC is specific to EMEs and is in contrast to the widely held conclusion that advanced economies monetary policy led to the taper tantrum sudden stops in EM, and more in line with recent reconsideration of the role played by US monetary policy during the taper tantrum (Clark et al, 2020). Third, the new role of oil prices in explaining stops is specific to EMEs, which thus be more sensitive to oil and commodity cycles.…”
Section: Drivers Of Extreme Capital Flow Episodesmentioning
confidence: 76%
“…First, surges are very poorly explained by global factors even in the pre-GFC period for advanced economies, while they do explain EME surges. Second, the drop of explanatory power of monetary policy post-GFC is specific to EMEs and is in contrast to the widely held conclusion that advanced economies monetary policy led to the taper tantrum sudden stops in EM, and more in line with recent reconsideration of the role played by US monetary policy during the taper tantrum (Clark et al, 2020). Third, the new role of oil prices in explaining stops is specific to EMEs, which thus be more sensitive to oil and commodity cycles.…”
Section: Drivers Of Extreme Capital Flow Episodesmentioning
confidence: 76%
“…Given that many developing economies are commodity exporters, commodity prices have been found to play a role in influencing foreign investment in these countries. For example, Clark et al (2016) found a significant and positive relationship between changes in commodity prices and net capital inflows in emerging market economies. Figure 4 illustrates a strong relationship between commodity prices and capital inflows to low-income SSAn countries.…”
Section: Factors Influencing Capital Flows To Middle-income Ssamentioning
confidence: 99%
“…Source: Data stream, FRED Federal Reserve Bank International portfolio investments (according to direct investments and other investments) are capital flows that are most sensitive to interest rate which are determined by the central banks of developed countries (Lim and Mohapatra, 2016). In mid 2013, the forecast of an increase in FED's interest rates has caused the loss of asset prices and the capital inflow for developing countries (Clark et al, 2016). Developing countries have been directly affected from the developed countries' monetary policies.…”
Section: Graph 1 Gvz -Ovx and Fed Funds Rate Underlie On The Global Risk Perceptionmentioning
confidence: 99%
“…Graph-1 depicts the time series of OVX, GVZ, VIX and the FED effective funds rates over the years. The changes in the VIX which is considered as a risk measure in the global sense (Siriopoulos ve Fassas, 2012;Clark et al, 2016;Kurt-Cihangir, 2018) is one of the primary aspect influencing the decisions of the financial units. An increase in VIX that means an increase in the perception of risk in the global sense, in which case, the financial units show a tendency towards more stable markets/investment instruments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation